THE USE OF THE METHOD OF RADIO-THERMAL IMAGING TECHNOLOGY TO SEARCH FOR LITHIUM ORE DEPOSITS - Комсулов, ​​Х.; Шель, В.; Багрянцев, В.; Родной, В.; Степченко, В. (SWorldJournal, 2021)
The possibilities of the method of Radio-Thermal Imaging Technology for the search for deposits of lithium ores are considered on the example of the Polokhovsky deposit of the Polokhovsky crystalline massif. Geothermal sections show the vertical geologica